A honeycomb ceramic structure and its preparation method and use

By grading and combining inorganic particle particles and materials on the honeycomb ceramic outer skin, its resistance to thermal shock, acid resistance and high temperature resistance after injecting acid, it solves the problems of easy shedding and insufficient resistance in the existing technology, and achieves stability Application and efficient production.

CN116903394BActive Publication Date: 2024-12-31SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310690493.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-31
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

The existing honeycomb ceramics are not resistant to thermal shock and acid resistance in harsh motor vehicles. Especially after the catalyst is applied, the outer skin is prone to fall off or powder, and the high temperature resistance after acid soaking is poor, making it difficult to achieve excellent results. Take into account multiple performances.

Method used

By grading the inorganic particles in the outer skin of the honeycomb ceramic structure, the particle size distribution index and particle size ratio of the first, second and third-level inorganic particles is regulated, and combined with organic and inorganic binders are enhanced Fiber improves the heat impact resistance, acid resistance and high temperature resistance of the outer skin after injecting acid.

Benefits of technology

It realizes the high thermal shock resistance, acid resistance and high temperature resistance of honeycomb ceramic outer skin, ensures the stability and strength of the product during use, avoids the problem of cracking and powdering of the outer skin after coating, and meets the Demand from downstream manufacturers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903394B_ABST
    Figure CN116903394B_ABST
Patent Text Reader

Abstract

The present invention provides a honeycomb ceramic structure and a preparation method and use thereof. The raw materials of the outer skin in the honeycomb ceramic structure include first-stage inorganic particles, second-stage inorganic particles, a binder, reinforcing fibers and a solvent; the small particle size distribution index Dfs of the first-stage inorganic particles is 0.25-0.84, and the large particle size distribution index Dfl is 0.25-0.80; the small particle size distribution index Dfs of the second-stage inorganic particles is 0.28-0.70, and the large particle size distribution index Dfl is 0.26-0.72. The present invention makes the outer skin have better thermal shock resistance by performing particle grading, and also has better acid resistance and high temperature resistance after acid soaking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of honeycomb ceramics and relates to a honeycomb ceramic structure and a preparation method and application thereof. Background Art

[0002] Honeycomb ceramics are widely used in the field of motor vehicle exhaust purification. Due to the multiple limitations of the large-diameter honeycomb ceramic carrier molding and sintering process, it is currently difficult to achieve one-time molding. Therefore, most honeycomb ceramics are mainly composed of a honeycomb body and an outer skin. The harsh motor vehicle use environment places higher requirements on the use temperature of honeycomb ceramics, including the honeycomb body and the outer skin, which must have better thermal shock resistance. When supplied to downstream catalyst manufacturers and packaging manufacturers for catalyst coating and packaging, the coating slurry is acidic, which can easily damage the outer skin structure, resulting in partial shedding or powdering of the outer skin. After the catalyst is coated, it will be roasted to burn off the organic binder in the outer skin, causing secondary damage to the outer skin. Therefore, the acid resistance of the honeycomb ceramic outer skin and the high temperature resistance after acid soaking are also key performance inspection points, which requires the outer skin to have high strength. How to achieve high thermal shock resistance and high strength of the outer skin is the key to ensuring the continuous and stable application of the honeycomb structure, but there is currently no patent that provides a solution to this key problem.

[0003] CN112608627A discloses a low thermal expansion honeycomb ceramic outer peripheral coating material, which is made of multi-grade spherical silicon powder, organic binder, inorganic binder, ceramic fiber, and deionized water. The thermal expansion of the outer skin is reduced by relying on the low thermal expansion of the multi-grade spherical silicon itself and the microcrack morphology. However, this method does not mention the effect on the acid resistance of the honeycomb ceramic outer skin and the high temperature resistance after acid soaking; Publication No. CN113429214B discloses a skinning mud material for honeycomb ceramics, which uses a mixture of aluminum silicate fiber and graphite fiber as reinforcing fiber. The product's thermal shock resistance can be increased to 650°C, but when used at a high temperature difference of more than 700°C, there is still a risk of cracking, and the effect on the acid resistance of the honeycomb ceramic outer skin and the high temperature resistance after acid soaking is also not mentioned. CN103044031B discloses a method for preparing honeycomb ceramics with high skin firmness. The invention uses phosphate solution for the skinning of honeycomb ceramics to improve the strength of the prepared skin. Although the invention mentions the acid resistance of the skin, it only examines whether the skin softens after being soaked in an acid solution, and does not mention the high temperature resistance of the skin after acid soaking.

[0004] Therefore, how to obtain a honeycomb ceramic structure with excellent thermal shock resistance, excellent acid resistance and high temperature resistance after acid soaking is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The object of the present invention is to provide a honeycomb ceramic structure and its preparation method and use. The present invention performs particle grading on inorganic particles in the outer skin of the honeycomb ceramic structure so that the outer skin has better thermal shock resistance, better acid resistance and high temperature resistance after acid soaking.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a honeycomb ceramic structure, comprising a honeycomb ceramic body and a skin coated on the surface of the honeycomb ceramic body; the raw materials of the skin include first-stage inorganic particles, second-stage inorganic particles, a binder, reinforcing fibers and a solvent;

[0008] Among them, the small particle size distribution index Dfs of the first-level inorganic particles is 0.25-0.84, and the large particle size distribution index Dfl is 0.25-0.80; the small particle size distribution index Dfs of the second-level inorganic particles is 0.28-0.70, and the large particle size distribution index Dfl is 0.26-0.72; Dfs=(D50-D10) / D50, Dfl=(D90-D50) / D90.

[0009] For example, the Dfs of the first stage inorganic particles may be 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.45, 0.47, 0.5, 0.55, 0.56, 0.57, 0.58, 0.6, 0.63, 0.64, 0.65, 0.7, 0.74, 0.75, 0.8 or 0.84, etc., and the Dfl of the first stage inorganic particles may be 0.25, 0.28, 0.3, 0.33, 0.35, 0.4, 0.42, 0.45, 0.5, 0.52, 0.5, 0.59, 0.6, 0.63, 0.65, 0.7, 0.74, 0.75, 0.8 or 0.84, etc. , 0.7, 0.72, 0.75 or 0.8, etc.; the Dfs of the second-stage inorganic particles can be 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.45, 0.5, 0.54, 0.55, 0.6, 0.61, 0.62, 0.64, 0.65 or 0.7, and the Dfl of the second-stage inorganic particles can be 0.26, 0.3, 0.33, 0.35, 0.36, 0.4, 0.45, 0.5, 0.52, 0.53, 0.55, 0.6, 0.62, 0.64, 0.65, 0.66, 0.7 or 0.72, etc. In the present invention, by performing particle grading on the inorganic particles in the outer skin of the honeycomb ceramic structure, the small particle size distribution index Dfs and the large particle size distribution index Dfl of the first-stage inorganic particles and the second-stage inorganic particles are regulated, so that the outer skin has better thermal shock resistance, and also has better acid resistance and high temperature resistance after acid soaking, which can ensure that the product meets the use requirements of downstream manufacturers, such as ensuring that the catalyst manufacturer does not crack after coating the product, the skin does not fall off, and powderizes, and the packaging manufacturer does not break the product skin during the packaging process, and can solve the problem of cracking of the outer skin and the body of the product due to poor thermal shock resistance during the actual application of the product, thereby ensuring the stability of the application process.

[0010] Preferably, the raw materials of the outer skin also include third-level inorganic particles, the small particle size distribution index Dfs of the third-level inorganic particles is 0.51-0.93, and the large particle size distribution index Dfl is 0.52-0.91. The Dfs of the third-level inorganic particles can be 0.51, 0.55, 0.59, 0.6, 0.62, 0.63, 0.65, 0.7, 0.75, 0.78, 0.8, 0.84, 0.85, 0.9 or 0.93, and the Dfl of the third-level inorganic particles can be 0.52, 0.55, 0.58, 0.6, 0.61, 0.64, 0.65, 0.67, 0.7, 0.75, 0.77, 0.8, 0.81, 0.84, 0.87, 0.9 or 0.91, etc.

[0011] In the present invention, adding third-level inorganic particles to the raw materials of the outer skin can better realize the excellent acid resistance of the honeycomb ceramic outer skin and the high temperature resistance after acid soaking, and further adjust its small particle size distribution index and large particle size distribution index, and grading with the first-level inorganic particles and the second-level inorganic particles, to obtain a honeycomb ceramic outer skin that can take into account multiple properties such as thermal shock resistance, acid resistance and high temperature resistance after acid soaking.

[0012] Preferably, the small particle size distribution index Dfs of the first-stage inorganic particles is 0.35-0.75, and the large particle size distribution index Dfl is 0.33-0.72; the small particle size distribution index Dfs of the second-stage inorganic particles is 0.32-0.64, and the large particle size distribution index Dfl is 0.30-0.66; the small particle size distribution index Dfs of the third-stage inorganic particles is 0.59-0.85, and the large particle size distribution index Dfl is 0.61-0.84.

[0013] Further preferably, the small particle size distribution index Dfs of the first-stage inorganic particles is 0.38-0.68, and the large particle size distribution index Dfl is 0.35-0.62; the small particle size distribution index Dfs of the second-stage inorganic particles is 0.42-0.61, and the large particle size distribution index Dfl is 0.45-0.62; the small particle size distribution index Dfs of the third-stage inorganic particles is 0.63-0.78, and the large particle size distribution index Dfl is 0.64-0.81.

[0014] In the present invention, after further screening of the small particle size distribution index Dfs and the large particle size distribution index Dfl of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles, the amount of powder loss of the skin after heat shock, the amount of powder loss of the acid-soaked product and the amount of powder loss of the acid-soaked product after heat shock are lower, indicating that it can further improve the skin strength while ensuring the thermal shock performance.

[0015] Preferably, the particle size ratio D of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (6.67-100.00):(1.11-20.00):1.00, preferably (8.75-63.33):(1.50-10.67):1.00, and further preferably (11.43-45.00):(2.14-7.00):1.00.

[0016] For example, the particle size ratio D may be 6.67:1.11:1, 20:5:1, 30:5:1, 32.5:5:1, 37.5:5:1, 47.5:5:1, 100:5:1, 50:20:1 or 100:20:1, etc.

[0017] In the present invention, the particle size ratio D of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is in the range of (6.67-100.00):(1.11-20.00):1.00, which can better achieve the high thermal shock resistance and high strength of the product. If it is not within this range, the thermal shock performance of the product will deteriorate, and the outer skin strength will decrease after coating, resulting in shedding and powdering. Further, when it is in the range of (11.43-45.00):(2.14-7.00):1.00, it is more conducive to improving the outer skin strength of the product and ensuring that the outer skin of the product has higher strength after coating.

[0018] Preferably, the weight ratio W of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (0.48-0.87):(0.10-0.40):(0-0.30), preferably (0.53-0.84):(0.15-0.35):(0.03-0.25), and further preferably (0.58-0.78):(0.18-0.31):(0.05-0.22).

[0019] For example, the weight ratio W may be 0.75:0.15:0.1, 0.50:0.40:0.10, 0.55:0.30:0.15, 0.60:0.25:0.15, 0.60:0.10:0.30, 0.70:0.10:0.20 or 0.80:0.20:0, etc.

[0020] In the present invention, when the weight ratio W of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is not in the range of (0.48-0.87):(0.10-0.40):(0-0.30), the slurry coating property will be poor, the thermal shock performance will be deteriorated, and the acid resistance and high temperature resistance after acid soaking will be deteriorated, thereby failing to achieve a balance of multiple performances. When W is further limited to (0.58-0.78):(0.18-0.31):(0.05-0.22), it is more conducive to improving the outer skin slurry coating property and thermal shock performance.

[0021] Preferably, the D50 of the first-stage inorganic particles is 60-200 μm, the D50 of the second-stage inorganic particles is 10-40 μm, and the D50 of the third-stage inorganic particles is 2-9 μm.

[0022] For example, the D50 of the first-stage inorganic particles can be 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm, etc.; the D50 of the second-stage inorganic particles can be 10μm, 12.5μm, 15μm, 17.5μm, 20μm, 22.5μm, 25μm, 27.5μm, 30μm, 32.5μm, 35μm, 37.5μm or 40μm, etc.; the D50 of the third-stage inorganic particles can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm, etc.

[0023] More preferably, the D50 of the first-stage inorganic particles is 70-190 μm, the D50 of the second-stage inorganic particles is 12-32 μm, and the D50 of the third-stage inorganic particles is 3-8 μm.

[0024] More preferably, the D50 of the first-stage inorganic particles is 80-180 μm, the D50 of the second-stage inorganic particles is 15-28 μm, and the D50 of the third-stage inorganic particles is 4-7 μm.

[0025] In the present invention, by limiting the D50 of the first-stage inorganic particles to 60-200 μm, the D50 of the second-stage inorganic particles to 10-40 μm, and the D50 of the third-stage inorganic particles to 2-9 μm, it is possible to better achieve a balance of thermal shock resistance, acid resistance, and high temperature resistance after acid soaking. If the D50 of any particle is higher than the upper limit, it is easy to cause the product strength to decrease, and if it is lower than the lower limit, it is easy to cause the thermal shock performance of the product to deteriorate.

[0026] Preferably, the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles include inorganic fused silica and / or cordierite powder.

[0027] Preferably, the binder includes an organic binder and an inorganic binder.

[0028] Preferably, the amount of the organic binder added is 0.002 to 0.025 of the total mass of the first, second and third stage inorganic particles, for example, 0.002, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.013, 0.015, 0.018, 0.020, 0.023 or 0.025, etc., preferably 0.004 to 0.022, and more preferably 0.006 to 0.019.

[0029] Preferably, the organic binder includes any one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose or ethyl cellulose, or a combination of at least two thereof.

[0030] Preferably, the amount of the inorganic binder added is 0.10 to 0.50 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles, such as 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.26, 0.29, 0.3, 0.32, 0.35, 0.38, 0.4, 0.43, 0.45, 0.48 or 0.5, etc., preferably 0.15 to 0.45, more preferably 0.18 to 0.40;

[0031] Preferably, the inorganic binder includes aluminum sol and / or silica sol.

[0032] Preferably, the added amount of the reinforcing fiber is 0.010-0.080 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles, for example, 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070 or 0.080, etc., preferably 0.015-0.070, more preferably 0.020-0.060.

[0033] Preferably, the reinforcing fiber includes any one of alumina fiber, mullite fiber, aluminum silicate fiber, wollastonite fiber, zirconia fiber, quartz fiber or silicon carbide fiber, or a combination of at least two thereof.

[0034] Preferably, the amount of the solvent added is 0.10 to 0.40 of the total mass of the first, second and third stage inorganic particles, for example, 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.27, 0.29, 0.3, 0.33, 0.35, 0.38 or 0.4, etc., preferably 0.13 to 0.35, and more preferably 0.15 to 0.30.

[0035] Preferably, the solvent comprises water.

[0036] In a second aspect, the present invention provides a method for preparing the honeycomb ceramic structure as described in the first aspect, the preparation method comprising the following steps:

[0037] (1) mixing first-stage inorganic particles, second-stage inorganic particles, a binder, reinforcing fibers, and a solvent to obtain a slurry of the outer skin;

[0038] (2) The skin slurry is applied to the surface of a honeycomb ceramic body to obtain the honeycomb ceramic structure.

[0039] The preparation method provided by the present invention has good fluidity of the slurry of the outer skin, is easy to scrape and apply, has a smooth outer skin state, has high production efficiency, and the preparation method is simple and easy to implement.

[0040] Preferably, the slurry of the outer skin in step (1) further comprises third-level inorganic particles.

[0041] Preferably, the method for preparing the outer skin slurry in step (1) comprises:

[0042] S1: mixing first-stage inorganic particles, second-stage inorganic particles and third-stage inorganic particles to obtain a multi-stage inorganic particle mixed powder;

[0043] S2: first mixing the multi-stage inorganic particle mixed powder, the organic binder and the reinforcing fiber described in S1 to obtain a mixed powder;

[0044] The inorganic binder and the solvent are mixed for a second time to obtain a mixed liquid material;

[0045] S3: adding the mixed liquid material described in S2 into the mixed powder material and mixing again to obtain a skin slurry.

[0046] Preferably, the coating in step (2) is followed by drying.

[0047] The drying process in the present invention can be performed at room temperature.

[0048] Preferably, the drying time is 20 to 30 h, for example, 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h or 30 h.

[0049] Preferably, the mixing time in step S1 is 2 to 10 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc., preferably 3 to 6 min.

[0050] Preferably, the first mixing time in step S2 is 10 to 25 min, for example, 10 min, 13 min, 15 min, 18 min, 20 min, 23 min or 25 min, etc., preferably 12 to 20 min.

[0051] Preferably, the time for remixing in step S3 is 15 to 30 min, for example, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min or 30 min, etc., preferably 18 to 27 min.

[0052] In a third aspect, the present invention further provides a use of a honeycomb ceramic structure, which includes using the honeycomb ceramic structure described in the first aspect for exhaust gas purification.

[0053] Relative to the prior art, the present invention has the following beneficial effects: in the present invention, by carrying out particle grading to the inorganic particles in the honeycomb ceramic structure skin, regulating the small particle size distribution index Dfs and the large particle size distribution index Dfl of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles, the skin is made to have a more excellent thermal shock resistance, and also has a more excellent acid resistance and high temperature resistance after acid soaking, it is possible to ensure that the product meets the use requirements of downstream manufacturers, such as ensuring that the catalyst manufacturer does not crack after coating the product, the skin does not fall off, and the powderization, the packaging manufacturer packaging process product skin is not broken, and the product can be solved in the actual application process, due to the problem of cracking of the skin and the body caused by poor thermal shock resistance, ensuring that the application process is stable. And the slurry fluidity of the skin is good, it is easy to scrape and apply, the skin state is flat, the production efficiency is high, the overall preparation process is simple to operate, and it is easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a performance test comparison chart of the powder loss of the honeycomb ceramic structure provided by Examples 1-20 and Comparative Examples 1-2 after thermal shock resistance.

[0055] Figure 2 This is a performance test comparison chart of the powder loss of the honeycomb ceramic structure provided by Example 1-20 and Comparative Example 1-2 after acid soaking.

[0056] Figure 3 This is a performance test comparison chart of the powder loss of the honeycomb ceramic structure provided by Example 1-20 and Comparative Example 1-2 after acid soaking and then thermal shock resistance. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Examples 1-20 and Comparative Examples 1-2

[0059] Examples 1-20 and Comparative Examples 1-2 both provide a honeycomb ceramic structure, which includes a honeycomb ceramic body and a skin coated on the surface of the honeycomb ceramic body; the raw materials of the skin are composed of first-level inorganic particles, second-level inorganic particles, third-level inorganic particles, organic binder, inorganic binder, reinforcing fiber and water, and its specific parameters and types of substances are shown in Table 1.

[0060] Among them, the small particle size index Dfs = (D50-D10) / D50, the large particle size index Dfl = (D90-D50) / D90; the particle size ratio D is the ratio of the particle sizes of the first-level inorganic particles, the second-level inorganic particles and the third-level inorganic particles; the weight ratio W is the weight ratio of the first-level inorganic particles, the second-level inorganic particles and the third-level inorganic particles; the weight proportions of the organic binder, the inorganic binder, the reinforcing fiber and the solvent are all 1 (here 1 is the total mass of the first-level inorganic particles, the second-level inorganic particles and the third-level inorganic particles).

[0061] Particle size test: Malvern Mastersizer 3000 was used to perform D10, D50, and D90 tests on multi-grade inorganic particles using laser diffraction.

[0062] Table 1

[0063]

[0064]

[0065]

[0066]

[0067]

[0068] Under the conditions of the above parameter ranges, Examples 1-20 and Comparative Examples 1-2 also provide a method for preparing a honeycomb ceramic structure, and the preparation method is as follows:

[0069] (1) mixing first-stage fused silica particles, second-stage fused silica particles, and third-stage fused silica particles according to a weight ratio factor W for a mixing time of 3 min to obtain a multi-stage fused silica mixed powder;

[0070] (2) mixing the multi-stage fused silica particles, methyl cellulose, and wollastonite fibers in dry powder according to the mass fractions for a mixing time of 15 min to obtain a mixed dry powder;

[0071] The silica sol and pure water are mixed evenly to obtain a mixed liquid material;

[0072] (3) adding the liquid obtained in step (2) to the mixed dry powder obtained in step (2), stirring for 20 minutes to obtain a slurry of the outer skin;

[0073] (4) The outer skin slurry obtained in step (3) is scraped and coated on the outer periphery of the honeycomb ceramic body, and dried at room temperature to obtain a honeycomb structure with an outer skin.

[0074] The specific values ​​of the drying time in Examples 1-20 and Comparative Examples 1-2 are shown in Table 2.

[0075] Table 2

[0076]

[0077]

[0078] The honeycomb ceramic structures provided in Examples 1-20 and Comparative Examples 1-2 were subjected to performance tests, including coating properties, thermal shock resistance, acid resistance, and high temperature resistance after acid soaking. The specific test conditions were:

[0079] 1. Coating property of the outer skin material on the outer periphery of the honeycomb ceramic blank: After the outer surface of the honeycomb ceramic blank is ground to a standard size, it is placed on the rotating fixture of the skin grafting machine. The scraper of the skin grafting machine scrapes the outer skin slurry on the outer periphery of the honeycomb ceramic blank. After scraping, the coating property is evaluated by visually observing the outer periphery formed. The situation where it is easy to scrape and the outer periphery is flat is represented by A, and the situation where it is difficult to scrape and the outer periphery is uneven is represented by B.

[0080] 2. Acid resistance test of the outer skin: The acid resistance of the outer skin is characterized by the amount of powder loss after the outer skin is soaked in acid and dried in the shade. Low powder loss indicates strong acid resistance, while high powder loss indicates poor acid resistance. Prepare a hydrochloric acid solution with a pH of 5, soak the honeycomb ceramic body with the outer skin in the hydrochloric acid solution for 10 minutes, and then dry it in the shade to test the powder loss. The case where the powder loss range is 0-0.025g is represented as A, and the case where the powder loss is greater than 0.025g is represented as B;

[0081] 3. Test of high temperature resistance of the outer skin after acid soaking: The high temperature resistance of the outer skin after acid soaking is characterized by the amount of powder loss after the outer skin is acid soaked, dried in the shade and roasted. Low powder loss indicates strong high temperature resistance after acid soaking, and high powder loss indicates poor high temperature resistance after acid soaking. Prepare a hydrochloric acid solution with a pH of 5, soak the honeycomb ceramic body with the outer skin in the hydrochloric acid solution for 10 minutes, then put the shade-dried honeycomb ceramic body into a 650°C muffle furnace, keep it warm for 30 minutes, take it out, cool it to room temperature (25°C), and then test the powder loss. The case where the powder loss range is 0-0.025g is represented as A, and the case where the powder loss is greater than 0.025g is represented as B;

[0082] 4. Use a muffle furnace to test the thermal shock resistance. Put the dried honeycomb structure into a resistance furnace that has reached the specified temperature. After keeping warm for 30 minutes, take out the honeycomb structure from the resistance furnace and immediately observe whether the skin and end faces are cracked. If no cracking is found, cool it to room temperature (25°C) and then put it back into the furnace. Repeat the above process three times. If cracking is found, stop the test. If no cracking is found, raise the temperature of the resistance furnace by 50°C and repeat the above process three times. The temperature at which cracking occurs is used as the evaluation standard. The case where the cracking temperature is ≥800°C is represented as A, and the case where the cracking temperature is <800°C is represented as B.

[0083] Sheath performance test results: Sheath materials whose performance is within the A standard range are evaluated as A, and sheath materials that do not meet any A evaluation standard are regarded as B. The specific test results are shown in Table 3.

[0084] Table 3

[0085]

[0086]

[0087] Combination Figure 1-3 ( Figure 1 A performance test comparison chart of the powder loss of the honeycomb ceramic structure provided by Examples 1-20 and Comparative Examples 1-2 after thermal shock resistance is shown; Figure 2 A performance test comparison chart of the powder loss of the honeycomb ceramic structure provided by Example 1-20 and Comparative Example 1-2 after acid soaking is shown; Figure 3 The performance test comparison diagram of the powder loss of the honeycomb ceramic structures provided by Examples 1-20 and Comparative Examples 1-2 after acid soaking and then thermal shock resistance is shown. It can be seen from the data results in Tables 1 to 3 that:

[0088] From the data results of Examples 1 to 15, it can be seen that the outer skin materials obtained by particle grading of multi-grade inorganic particles within the scope of the present invention all have good coating properties and can improve production efficiency. Figure 1 It can be seen that the skin material has excellent effect, and can stably achieve three rapid coolings at 750℃ to 850℃ without cracks. The powder loss of the outer skin of the honeycomb ceramic body after thermal shock can be maintained at 0.007 to 0.022g, which is A level and has high strength. At the same time, the acid resistance of the honeycomb ceramic structure provided by the present invention is also relatively excellent. After being immersed in an acid solution of pH=5 for 10 minutes, the Figure 2 It can be seen that the powder loss of the outer skin after acid soaking is 0.005-0.023g, which is still at the A level, indicating that its strength has not been significantly deteriorated; the honeycomb ceramic body after acid soaking and air drying was put into a 650℃ muffle furnace, kept warm for 30 minutes, and then taken out and cooled to room temperature (25℃) for another powder loss test. Figure 3 It can be seen that its strength is still relatively high, indicating that the high temperature resistance of the outer skin after acid soaking is good.

[0089] It can be seen from the data results of Example 1 and Example 16 that when the particle size ratio factor of the first-stage inorganic particles is higher than the upper limit, that is, when the particle size ratio D is not within the maximum numerical protection range provided by the present invention, the obtained outer skin material has good coating properties, but its thermal shock resistance, acid resistance and high temperature resistance after acid soaking are also poor, that is, it is impossible to achieve a balance between multiple performances.

[0090] It can be seen from the data results of Example 1 and Examples 17-18 that when the D50 of the first-level inorganic particles, the second-level inorganic particles or the third-level inorganic particles is not within the maximum numerical protection range provided by the present invention, although the acid resistance and high temperature resistance after acid soaking are good, the coating performance of the honeycomb ceramic structure skin is poor, and the thermal shock resistance does not meet the requirements, and it is also impossible to achieve a balance of multiple performances.

[0091] It can be seen from the data results of Examples 1 and 19-20 that when the weight ratio W is not within the maximum numerical protection range provided by the present invention (excluding the third-level inorganic particles), the outer skin performance of the product does not meet the requirements. The weight ratio W of Example 19 exceeds the lower limit of the preferred range of the present invention. Although the acid resistance and high temperature resistance of the honeycomb ceramic structure outer skin after acid soaking are good, the coating performance is poor, and the thermal shock resistance does not meet the requirements; the weight ratio W of Example 20 exceeds the upper limit of the preferred range of the present invention. Although the obtained outer skin material has good coating properties, the thermal shock resistance, acid resistance and high temperature resistance after acid soaking do not meet the requirements.

[0092] It can be seen from the data results of Example 1 and Comparative Example 1 that when the first-level inorganic particles, the second-level inorganic particle size or the third-level inorganic particles are not subjected to the particle grading provided by the present invention, and do not satisfy the small particle size index Dfs and the large particle size index Dfl provided by the present invention, the obtained outer skin has good coatability, but poor thermal shock resistance, acid resistance and high temperature resistance after acid soaking, and it is completely impossible to achieve the technical effect of the present invention that takes into account multiple performances of impact resistance, acid resistance and high temperature resistance after acid soaking.

[0093] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A honeycomb ceramic structure, characterized in that: The honeycomb ceramic structure comprises a honeycomb ceramic body and a skin coated on the surface of the honeycomb ceramic body; the raw materials of the skin comprise first-stage inorganic particles, second-stage inorganic particles, third-stage inorganic particles, a binder, reinforcing fibers and a solvent; Wherein, the small particle size distribution index Dfs of the first-stage inorganic particles is 0.25-0.84, and the large particle size distribution index Dfl is 0.25-0.80; The small particle size distribution index Dfs of the second-stage inorganic particles is 0.28-0.70, and the large particle size distribution index Dfl is 0.26-0.72; The small particle size distribution index Dfs of the third-stage inorganic particles is 0.51-0.93, and the large particle size distribution index Dfl is 0.52-0.91; Dfs=(D50-D10) / D50, Dfl=(D90-D50) / D90; The particle size ratio D of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (6.67-100.00): (1.11-20.00): 1.00; The weight ratio W of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (0.53-0.84): (0.15-0.35): (0.03-0.25); The D50 of the first-stage inorganic particles is 60-200 μm, the D50 of the second-stage inorganic particles is 10-40 μm, and the D50 of the third-stage inorganic particles is 2-9 μm; The first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles include inorganic fused silica and / or cordierite powder.

2. The honeycomb ceramic structure according to claim 1, characterized in that: The small particle size distribution index Dfs of the first-stage inorganic particles is 0.35~0.75, and the large particle size distribution index Dfl is 0.33~0.72; the small particle size distribution index Dfs of the second-stage inorganic particles is 0.32~0.64, and the large particle size distribution index Dfl is 0.30~0.66; the small particle size distribution index Dfs of the third-stage inorganic particles is 0.59~0.85, and the large particle size distribution index Dfl is 0.61~0.

84.

3. The honeycomb ceramic structure according to claim 2, characterized in that: The small particle size distribution index Dfs of the first-stage inorganic particles is 0.38~0.68, and the large particle size distribution index Dfl is 0.35~0.62; the small particle size distribution index Dfs of the second-stage inorganic particles is 0.42~0.61, and the large particle size distribution index Dfl is 0.45~0.62; the small particle size distribution index Dfs of the third-stage inorganic particles is 0.63~0.78, and the large particle size distribution index Dfl is 0.64~0.

81.

4. The honeycomb ceramic structure according to claim 1, characterized in that: The particle size ratio D of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (8.75-63.33): (1.50-10.67): 1.

00.

5. The honeycomb ceramic structure according to claim 4, characterized in that: The particle size ratio D of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (11.43-45.00):(2.14-7.00):1.

00.

6. The honeycomb ceramic structure according to claim 1, characterized in that: The weight ratio W of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles is (0.58-0.78): (0.18-0.31): (0.05-0.22).

7. The honeycomb ceramic structure according to claim 1, characterized in that: The D50 of the first-stage inorganic particles is 70-190 μm, the D50 of the second-stage inorganic particles is 12-32 μm, and the D50 of the third-stage inorganic particles is 3-8 μm.

8. The honeycomb ceramic structure according to claim 7, characterized in that: The D50 of the first-stage inorganic particles is 80-180 μm, the D50 of the second-stage inorganic particles is 15-28 μm, and the D50 of the third-stage inorganic particles is 4-7 μm.

9. The honeycomb ceramic structure according to claim 1, characterized in that: The binder includes an organic binder and an inorganic binder.

10. The honeycomb ceramic structure according to claim 9, characterized in that: The amount of the organic binder added is 0.002-0.025 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

11. The honeycomb ceramic structure according to claim 10, characterized in that: The amount of the organic binder added is 0.004-0.022 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

12. The honeycomb ceramic structure according to claim 11, characterized in that: The amount of the organic binder added is 0.006-0.019 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

13. The honeycomb ceramic structure according to claim 9, characterized in that: The organic binder includes any one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose or ethyl cellulose, or a combination of at least two thereof.

14. The honeycomb ceramic structure according to claim 9, characterized in that: The amount of the inorganic binder added is 0.10 to 0.50 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

15. The honeycomb ceramic structure according to claim 14, characterized in that: The amount of the inorganic binder added is 0.15-0.45 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

16. The honeycomb ceramic structure according to claim 15, characterized in that: The amount of the inorganic binder added is 0.18 to 0.40 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

17. The honeycomb ceramic structure according to claim 9, characterized in that: The inorganic binder includes aluminum sol and / or silica sol.

18. The honeycomb ceramic structure according to claim 1, characterized in that: The added amount of the reinforcing fibers is 0.010-0.080 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

19. The honeycomb ceramic structure according to claim 18, characterized in that: The added amount of the reinforcing fibers is 0.015 to 0.070 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

20. The honeycomb ceramic structure according to claim 19, characterized in that: The added amount of the reinforcing fibers is 0.020 to 0.060 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

21. The honeycomb ceramic structure according to claim 1, characterized in that: The reinforcing fiber includes any one of alumina fiber, mullite fiber, aluminum silicate fiber, wollastonite fiber, zirconia fiber, quartz fiber or silicon carbide fiber, or a combination of at least two thereof.

22. The honeycomb ceramic structure according to claim 1, characterized in that: The amount of the solvent added is 0.10 to 0.40 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

23. The honeycomb ceramic structure according to claim 22, characterized in that: The amount of the solvent added is 0.13-0.35 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

24. The honeycomb ceramic structure according to claim 23, characterized in that: The amount of the solvent added is 0.15-0.30 of the total mass of the first-stage inorganic particles, the second-stage inorganic particles and the third-stage inorganic particles.

25. The honeycomb ceramic structure according to claim 1, characterized in that: The solvent includes water.

26. A method for preparing a honeycomb ceramic structure according to any one of claims 1 to 25, characterized in that: The preparation method comprises the following steps: (1) mixing first-stage inorganic particles, second-stage inorganic particles, third-stage inorganic particles, a binder, reinforcing fibers, and a solvent to obtain a slurry of the outer skin; (2) The skin slurry is applied to the surface of a honeycomb ceramic body to obtain the honeycomb ceramic structure.

27. The method for preparing a honeycomb ceramic structure according to claim 26, characterized in that: The method for preparing the outer skin slurry in step (1) comprises: S1: mixing first-stage inorganic particles, second-stage inorganic particles and third-stage inorganic particles to obtain a multi-stage inorganic particle mixed powder; S2: first mixing the multi-stage inorganic particle mixed powder, the organic binder and the reinforcing fiber described in S1 to obtain a mixed powder; The inorganic binder and the solvent are mixed for a second time to obtain a mixed liquid material; S3: adding the mixed liquid material described in S2 into the mixed powder material and mixing again to obtain a skin slurry.

28. The method for preparing a honeycomb ceramic structure according to claim 26, characterized in that: The coating in step (2) is followed by drying.

29. The method for preparing a honeycomb ceramic structure according to claim 28, characterized in that: The drying time is 20 to 30 hours.

30. The method for preparing a honeycomb ceramic structure according to claim 27, characterized in that: The mixing time in step S1 is 2 to 10 minutes.

31. The method for preparing a honeycomb ceramic structure according to claim 30, characterized in that: The mixing time in step S1 is 3 to 6 minutes.

32. The method for preparing a honeycomb ceramic structure according to claim 27, characterized in that: The first mixing time in step S2 is 10 to 25 minutes.

33. The method for preparing a honeycomb ceramic structure according to claim 32, characterized in that: The first mixing time in step S2 is 12 to 20 minutes.

34. The method for preparing a honeycomb ceramic structure according to claim 27, characterized in that: The time for remixing in step S3 is 15 to 30 minutes.

35. The method for preparing a honeycomb ceramic structure according to claim 34, characterized in that: The time for remixing in step S3 is 18 to 27 minutes.

36. A use of a honeycomb ceramic structure, characterized in that: The use includes using the honeycomb ceramic structure according to any one of claims 1 to 25 for exhaust gas purification.